Research on Clustering Routing Algorithms in Wireless Sensor Networks - Qing Bian; Yan Zhang; Yanjuan Zhao (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
Compared with the traditional wireless networks, wireless sensor networks have energy constraints, low-data-rate of high redundant and data flow of high-to-one, and so on. Energy effectiveness is the key performance indicators of wireless sensor networks. Based on the analysis of energy management strategy in the wireless sensor networks, the main factors affecting energy consumption are: perceptual data, data processing and radio communications, the radio communication is the main part of energy consumption. In the wireless sensor networks, the realization of energy-efficiency could be improved while in the different layers of communication protocol stack. However, as the basis of the limitations of the physical layer, the improvement is focus on design and implementation of network-layer protocol. The researchers agreed that the clustering of nodes in wireless sensor networks is an effective program of energy conservation. This article dedicated to research the clustering routing algorithm in wireless sensor networks.